2020
DOI: 10.3389/fpls.2020.602455
|View full text |Cite
|
Sign up to set email alerts
|

Highly Reduced Plastid Genomes of the Non-photosynthetic Dictyochophyceans Pteridomonas spp. (Ochrophyta, SAR) Are Retained for tRNA-Glu-Based Organellar Heme Biosynthesis

Abstract: Organisms that have lost their photosynthetic capabilities are present in a variety of eukaryotic lineages, such as plants and disparate algal groups. Most of such non-photosynthetic eukaryotes still carry plastids, as these organelles retain essential biological functions. Most non-photosynthetic plastids possess genomes with varied protein-coding contents. Such remnant plastids are known to be present in the non-photosynthetic, bacteriovorous alga Pteridomonas danica (Dictyochophyceae, Ochrophyta), which, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…Plastids in photosynthetic and nonphotosynthetic Ochrophyta play crucial roles for various metabolisms such as glycolysis/gluconeogenesis, biosynthesis of fatty acids, lipids, amino acids, heme, riboflavin, isoprenoids, Fe–S clusters, and the pentose phosphate pathway ( Plaxton 1996 ; Kleffmann et al 2004 ; Kamikawa et al 2017 ; Dorrell et al 2019 ; Kayama et al 2020 ). Even in secondary heterotrophic ochrophytes that bear nonphotosynthetic plastids, transcriptomic analyses detect large numbers of transcripts for plastid functions and biogenesis ( Kamikawa et al 2017 ; Dorrell et al 2019 ; Kayama et al 2020 ). If A. sol possesses a metabolically active nonphotosynthetic plastid sharing the origin with plastids of Ochrophyta, at least some transcripts encoding proteins involved in the plastid biosynthesis should be detected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plastids in photosynthetic and nonphotosynthetic Ochrophyta play crucial roles for various metabolisms such as glycolysis/gluconeogenesis, biosynthesis of fatty acids, lipids, amino acids, heme, riboflavin, isoprenoids, Fe–S clusters, and the pentose phosphate pathway ( Plaxton 1996 ; Kleffmann et al 2004 ; Kamikawa et al 2017 ; Dorrell et al 2019 ; Kayama et al 2020 ). Even in secondary heterotrophic ochrophytes that bear nonphotosynthetic plastids, transcriptomic analyses detect large numbers of transcripts for plastid functions and biogenesis ( Kamikawa et al 2017 ; Dorrell et al 2019 ; Kayama et al 2020 ). If A. sol possesses a metabolically active nonphotosynthetic plastid sharing the origin with plastids of Ochrophyta, at least some transcripts encoding proteins involved in the plastid biosynthesis should be detected.…”
Section: Resultsmentioning
confidence: 99%
“…Ochrophyta is one of the most diverse groups of photosynthetic eukaryotes ( Adl et al 2019 ; Sibbald and Archibald 2020 ), including nonphotosynthetic species that have lost photosynthesis secondarily ( Kamikawa et al 2017 ; Dorrell et al 2019 ; Kayama et al 2020 ). The best-known Ochrophyta lineages are the unicellular diatoms (Bacillariophyceae) whose primary production in the ocean contributes almost 20% of the net global primary production ( Field et al 1998 ; Mann 1999 ) and the multicellular brown algae (Phaeophyceae) such as giant kelp, which support coastal ecosystems as habitats for aquatic animals ( Bringloe et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is also worth noting that this phylogenetic analysis of euglenid maturases might have revealed an additional case of acquisition of a maturase gene outside of euglenophytes, in a secondary red plastid lineage. We identified that a unique IEP of Dictyocha speculum (Dictyochophyceae, SAR), encoded within the only intron ever found among all six available plastid genomes of this group (Han et al, 2019; Kayama et al, 2020), is in fact a mat4 homologue, containing all three functional protein domains found in mat4c of Etl. eupharyngea and Etl.…”
Section: Resultsmentioning
confidence: 99%
“…Nitz4, the cryptophyte Cryptomonas paramecium and the dinoflagellate Crypthecodinium cohnii now depend on their plastids for haem synthesis (Hadariová et al ., 2018), similarly to the heterotrophic members of Archaeplastida mentioned earlier. In the free‐living bacterivorous dictyochophytes Pteridomonas spp., haem biosynthesis remains one of the last essential functions of the plastid and the expression of the only essential gene encoding tRNA glu (the substrate for the C5 pathway) appears to be the sole reason for the retention of its highly reduced genome (Kayama et al ., 2020).…”
Section: Haem Synthesis In Plastid‐bearing Eukaryotesmentioning
confidence: 99%